An expert system for the diagnosis of tank irrigated systems: a feasibility study - Oswald, O. (International Irrigation Management Institute, 1992)
Part of a thesis titled: "An expert system for the diagnosis of tank irrigated systems : a feasibility study". This working paper is an analysis intended to bring understanding of the system, to provide an evaluation of its performance with reference to some stated objectives and optionally to recommend how the expected objectives can be achieved by removing the bottlenecks in the system.